Study on Calculating, Designing and Manufacturing the Smart Infrared Drying System - Do, Thuy Khanh Linh; Chau, Thanh Tuan; Vu, Tran Khanh Linh; Nguyen, Tan Dung (Journal of Technical Education Science, 2022)
The infrared drying technology has been known as the energy saving technology. The infrared dried products keep their quality better than those dried by other normal methods. This research will present the results of calculating, designing, and manufactured the infrared drying system with the capacity of 12 kilograms materials per batch. The drying process is automatically controlled and measured by the computer program. After successfully manufactured, the drying system was used to dry the pineapple products with a thickness of 3 to 4 mm and followed by the drying modes: 69 °C of the drying temperature, 5 m/s of the rate of drying factors, and 5.0 hours of the drying time. The results showed that the energy cost was 2.013 kWh/kg of products lower than that of 3.8 kW/kg of products dried by the normal dryings, the moisture content reached 9.96 %, reduced products cost, and prolonged the self-life. The dried pineapple showed the bright yellow, natural odors, and better quality than that dried by normal methods. Thus, the manufactured drying system can improve the post-harvest preserving matters of Vietnamese agricultural products and lead to high economic efficiency.